Vaccines against Herpes zoster: Effectiveness, safety, and cost/benefit ratio - Ferahta, Nabila; Achek, Imene; Dubourg, Julie; Lang, Pierre-Olivier (La Presse médicale (1983), 2016)
A vaccination against herpes zoster and its complication is available in France since June 2015. Its exact benefit for public health is still controversial and its level of protection is not optimal. All those reasons seem to suggest a low acceptation rate from general practitioners. To evaluate the effectiveness, the safety, and the cost/benefit ratio of the vaccination against herpes zoster in people aged 50 year or over. Systematic review in Medline and PubMed with research by key words: "herpes zoster vaccine", "zoster vaccine" and "post herpetic neuralgia vaccine". Randomized and observational studies published in English and French language have been selected by two readers. On 1886 articles identified, 62 studies were included in this systematic review of which 21 randomized trials, 21 observational studies, and 17 medico-economic studies concerned the unadjuvanted vaccine. Considered studies showed an effectiveness of 50% against herpes zoster and 60% on post-herpetic neuralgia incidence of the unadjuvanted vaccine. Five randomized controlled studies were identified for the adjuvanted vaccine. The overall effectiveness of this vaccine was > 90% whatever the age of subjects including those over age 70 and 80. The medico-economic studies conducted in many countries have shown that vaccine policies were beneficial in individuals aged 60 years or over. Most of data of effectiveness, and tolerance result from 2 large controlled studies only (SPS and ZEST) for the unadjuvanted vaccine and only one for the adjuvanted vaccine. Despite controversy and few uncertainties, the vaccine significantly reduces herpes zoster and its complication incidence. In terms of public health objectives, it reduces the burden of the disease and has a positive medico-economic impact. Preliminary data concerning the adjuvanted vaccine, whilst very promising, are still too limited. Up to now, no group of people with particularly high risk of herpes zoster-related complication who will beneficiate the most of the vaccination has been identified yet and only an age criteria has been considered for the recommendation.